2011
DOI: 10.1016/j.immuni.2011.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Bcl6 Protein Expression Shapes Pre-Germinal Center B Cell Dynamics and Follicular Helper T Cell Heterogeneity

Abstract: The transcription factor Bcl6 is essential for the development of germinal center (GC) B cells and follicular helper T (Tfh) cells. However, little is known about in vivo dynamics of Bcl6 protein expression during and after development of these cells. By using a Bcl6 reporter mouse strain, we found that antigen-engaged B cells upregulated Bcl6 before clustering in GCs. Two-photon microscopic analysis indicated that Bcl6 upregulation in pre-GC B cells contributed to sustaining their interactions with helper T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
397
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(431 citation statements)
references
References 44 publications
31
397
1
2
Order By: Relevance
“…This is in accordance with the fact that T FH cells may downregulate Bcl6 over weeks after antigenic challenge. 56 Recently, Morita et al 52 shed light on the relationship between T FHC (CD4 1 CXCR5 1 ) and T FH cells and convincingly demonstrated that T FHC cells share functional, and to some extent phenotypic, properties of T FH cells present in the lymphoid organs of humans and mice, and constitute a subset of circulating pool of memory T FH cells. They found T FHC cells to be potent at providing help for B-cell responses, such as production of plasmablasts and promotion of class switching through IL-21.…”
Section: The Darker Side Of Follicular Helper T Cells S Shekhar and Xmentioning
confidence: 99%
“…This is in accordance with the fact that T FH cells may downregulate Bcl6 over weeks after antigenic challenge. 56 Recently, Morita et al 52 shed light on the relationship between T FHC (CD4 1 CXCR5 1 ) and T FH cells and convincingly demonstrated that T FHC cells share functional, and to some extent phenotypic, properties of T FH cells present in the lymphoid organs of humans and mice, and constitute a subset of circulating pool of memory T FH cells. They found T FHC cells to be potent at providing help for B-cell responses, such as production of plasmablasts and promotion of class switching through IL-21.…”
Section: The Darker Side Of Follicular Helper T Cells S Shekhar and Xmentioning
confidence: 99%
“…BCL6 up-regulation appears to be important for pre-GC B cell to form sustained interaction with cognate Tfh cells and move towards the center of the follicle. BCL6 seems to drive pre-GC B cell migration at least in part through directly inhibiting the trafficking factors Sphingosine 1-phosphate receptor 1 (S1PR1) and GPR183, which encodes G protein-coupled receptor 183 [21,31]. These new findings point to multifaceted biological functions of BCL6 in the GC response.…”
Section: Bcl6: a Master Transcriptional Regulator Of Gc B-cell Develomentioning
confidence: 96%
“…The first step towards GC formation is activation of naïve B cells by exogenous T-cell dependent antigen in the follicles of peripheral lymphoid tissues. Next, antigen-engaged B-cells migrate to the border between the follicles and the T cell zone or interfollicular zones, where they undergo proliferation and interact with cognate Tfh cells within 1-3 days after stimulation [18][19][20][21]. B-cells can then differentiate into extrafollicular plasma cells and leave the follicle to generate low-affinity antibodies, or alternatively can enter the GC pathway [22].…”
Section: Gc B Cell Development and B Cell Lymphomagenesismentioning
confidence: 99%
See 2 more Smart Citations